A convergent stereocontrolled synthesis of [3‐14C]solanesol†. (23rd September 2013) - Roe, Stephen J.; Oldfield, Mark F.; Geach, Neil; Baxter, Andrew
Abstract : In this communication, we report the synthesis of ~5 mCi of [3‐ 14 C]solanesol (1) prepared from ethyl [3‐ 14 C]acetoacetate and (all‐ E )‐octaprenyl bromide (2) in four steps, with a specific radioactivity of 19.83 mCi/mmol and with a chemical/stereochemical and radiochemical purity of ≥ 95%. (Figure 1 ). Position 3 of the chain was selected for 14 C labelling because of the metabolic stability of this position. Unlabelled (all‐ E )‐octaprenyl (18) (Scheme 4 ) necessary for this work was prepared via a convergent iterative 'allyl‐allyl' coupling approach of precursors easily derived from readily available inexpensive starting materials. 1 Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Solanesol (1 ), a major polyprenoid found in tobacco and an important intermediate to many valuable biochemicals has been prepared radiolabelled starting from ethyl [3‐ 14 C]acetoacetate and (all‐E)‐octaprenyl bromide (2 ) in 4 steps, with a specific radioactivity of 19.83mCi/mmol and with a chemical / stereochemical and radiochemical purity of ≥ 95%.